(In press) Inclusive Madrasah: Policy, Implementation and Realization for Students with Disabilities in South Kalimantan - Nisa, Uswatun (Indonesian Journal of Disability Studies, 2026)
Inclusive madrasah is a strategic policy of the Ministry of Religious Affairs as a progressive step to achieve equitable access to education that includes students with special needs and positive empowerment in a conductive environment. Madrasah is a means of education wrapped in Islamic values in its existence is expected to be able to accommodate the diverse needs of students with special needs. Based on the author’s research in the field, it was found that the implementation of inclusive madrasah in South Kalimantan Province has not been realized evenly in each district. Among 11 districts and 2 cities, only 1 city showed the implementation of 13 Ibtidaiyyah madrasah after previously being lined up as an inclusive madrasah model. This picture implicitly does not imply a steady change towards the actualization of the value of inclusivity in Muslim societies and discrimination against education has not yet found a solutive base. This research is a qualitative study with a case study approach at the Ministry of Religious Affairs of South Kalimantan Province in implementing inclusive schools began several years ago since this medium-term program was released by the center. In general, the Ministry of Religious has carried out follow-up circulars to each institution as a realization of inclusive-based madrasah mapping. The principle of synergy as a step to improve the quality of madrasah is carried out with special education school.